A case study of the use of the Six Thinking Hats to enhance the reflective practice of student teachers in Taiwan. Issue 5 (4th July 2021) - Chien, Chin-Wen
ABSTRACT: This study integrated Six Thinking Hats into the reflective practice of nine student teachers during their practicum in a teacher education programme in the northwest of Taiwan. Based on the analysis of the artifacts, interviews, and observations, this study had the following major findings. First, participants had a positive attitude toward the technique because participants' innovation, critical thinking, and problem solving were fostered. Second, participants' unfamiliarity with the Six Thinking Hats and the limited time they had to utilise the technique affected their ability to use it to its full potential. A framework was suggested to facilitate the integration of Six Thinking Hats into practicum and teacher education programmes.